Biota do solo em pastagem sob aplicação sucessiva de dejetos de suínos - Silva, Danni Maisa da (2015)
The successive use of pig slurry as a soil fertilizer on pasture areas is a common practice in southern Brazil. While there are economic benefits of reuse of waste, this practice poses serious environmental risks and can cause changes in the composition and activity of soil organisms. The soil organisms and microbiological soil quality indicators are very sensitive and allow the monitoring of the soil environment conditions. This work aimed to study the effect of the successive application of pig slurry in pasture areas on the composition, biological activity and microbiological soil quality. The study was conducted in Três Passos/RS in two harvest periods (winter and spring), in areas with use of manure 2 years ago (A2), 14 years (A14) and native forest (NF). In all areas we analyzed the composition of soil organisms through the use PROVID and TSBF, biological activity, using litter bags and bait blade test; was also evaluated the microbiological quality of the soil from the determination of carbon content in the microbial biomass, soil microbial respiration, metabolic quotient (qCO2) and activity of enzymes β Glycosidase, urease and Hydrolysis of Fluorescein diacetate (FDA). The successive use of pig slurry in the soil changed the biological characteristics, according to the same application time; influences the composition and diversity of soil fauna by increasing the total number of individuals, primarily springtails; the activity of soil biota is influenced by the collection time of the analysis and depth, and most especially up to 6 inches from the ground; the successive use of pasture in pig slurry does not influence the carbon biomass, microbial respiration and metabolic quotient were allowing the maintenance of the levels of microbiological soil quality in relation to native forest; the soil enzymatic activity was influenced by the use of pig slurry, and the urease and the hydrolysis of fluorescein diacetate (FDA) were sensitive to detect differences in the activity of soil microorganisms with the use of pig slurry while the enzyme β-glucosidase did not allow the differentiation between the studied areas.